Minimizing delays using collaborative decision making in air traffic management - Goh, Ming Xuan (2015)
With the increase in the demand for air travel over the past decade and the growing number of aircraft and flights in the air, resource limitations and its impact have become a cause of concern all around the world. National Aviation Authorities such as the Federal Aviation Administration in the United States along with industry partners and academic agencies have been working together in developing software tools and operational processes to relief airspace and airport congestion. One area of focus is that of Collaborative Decision Making (CDM) between the National Aviation Authority of a country and the Airline Operational Control Centres (AOCs). CDM aims to alleviate the congestion problem by sharing information between airlines and authority in hope of achieving higher efficiency in flight control and alternate routing during periods of congestion. In this report, the mathematical model developed by Bertsimas and Sarah Stock Patterson in one of their landmark research paper published in 1998 is adopted as the base model. Concepts of CDM are further explored and applied to the model in the form of alternate routing in single and dual origin-destination pairs. Special attention was given to utilize the sector capacity constraint in multiple route models without additional constraints or linearization methods proposed in the original research paper.